2015
DOI: 10.5194/acp-15-3077-2015
|View full text |Cite
|
Sign up to set email alerts
|

Properties and evolution of biomass burning organic aerosol from Canadian boreal forest fires

Abstract: Abstract. Airborne measurements of biomass burning organic aerosol (BBOA) from boreal forest fires reveal highly contrasting properties for plumes of different ages. These measurements, performed using an Aerodyne Research Inc. compact time-of-flight aerosol mass spectrometer (C-ToF-AMS) during the BORTAS (quantifying the impact of BOReal forest fires on Tropospheric oxidants over the Atlantic using Aircraft and Satellites) experiment in the summer of 2011, have been used to derive normalised excess organic ae… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 74 publications
12
83
0
Order By: Relevance
“…For example, fast (within several hours) and strong SOA formation events (associated with an increase in NEMR by a factor of 2 and more) in savannas were reported by Yokelson et al (2009) and Vakkari et al (2014). However, Akagi et al (2012) reported a net increase in the OA NEMR of only about 20 % over 4 h in the case of chaparral fires in California, and Jolleys et al (2015) observed higher NEMR values closer to the source than in aged plumes from Canadian fires. Overall, the available laboratory studies and atmospheric observations suggest that the SOA formation in the real atmosphere can be strongly influenced by the type of fuel and conditions of burning, as well as by the atmospheric conditions of BB aerosol evolution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fast (within several hours) and strong SOA formation events (associated with an increase in NEMR by a factor of 2 and more) in savannas were reported by Yokelson et al (2009) and Vakkari et al (2014). However, Akagi et al (2012) reported a net increase in the OA NEMR of only about 20 % over 4 h in the case of chaparral fires in California, and Jolleys et al (2015) observed higher NEMR values closer to the source than in aged plumes from Canadian fires. Overall, the available laboratory studies and atmospheric observations suggest that the SOA formation in the real atmosphere can be strongly influenced by the type of fuel and conditions of burning, as well as by the atmospheric conditions of BB aerosol evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Cubison et al, 2011) (the ratio of the organic signal at m/z 60 to the total organic signal in the component mass spectrum) from oxidative decay of species such as levoglucosan. The f 60 vs. f 44 space (Cubison et al, 2011) is therefore used to characterise the evolution of biomass burning aerosols, with data from many studies exhibiting a negative correlation between f 44 and f 60 (Cubison et al, 2011;Ortega et al, 2013;Jolleys et al, 2014a). If the two SFOA factors represented different levels of processing of the same fuel type under similar conditions then SFOA1 would be expected to have higher f 44 and lower f 60 compared SFOA2.…”
Section: Role Of Atmospheric Processingmentioning
confidence: 99%
“…Although these studies primarily characterized fresh smoke emissions, there was no clear consensus whether PM mass increases (Hobbs et al, 2003;Reid et al, 2005;Yokelson et al, 2009;Vakkari et al, 2014;Briggs et al, 2016) or stays the same (Akagi et al, 2012;Jolleys et al, 2015;May et al, 2015) (Wigder et al, 2013;Laing et al, 2016). Similar wide ranges have been observed in aged WF plume ΔOA/ΔCO (OA = organic aerosol, which makes up ~95% of PM 2.5 mass) (Jolleys et al, 2012;Sakamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%